2011
DOI: 10.1029/2011gl047415
|View full text |Cite
|
Sign up to set email alerts
|

The composition and structure of the Enceladus plume

Abstract: [1] The Cassini Ultraviolet Imaging Spectrograph (UVIS) observed an occultation of the Sun by the water vapor plume at the south polar region of Saturn's moon Enceladus. The Extreme Ultraviolet (EUV) spectrum is dominated by the spectral signature of H 2 O gas, with a nominal line-of-sight column density of 0.90 ± 0.23 × 10 16 cm −2 (upper limit of 1.0 × 10 16 cm −2 ). The upper limit for N 2 is 5 × 10 13 cm −2 , or <0.5% in the plume; the lack of N 2 has significant implications for models of the geochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(154 citation statements)
references
References 23 publications
5
149
0
Order By: Relevance
“…Plume variability at the ∼1 order of magnitude level has been documented based on INMS and magnetic field data Saur et al 2008). In contrast, UVIS occultations (Hansen et al 2011) indicate a remarkable stability of the source rate, with variations as low as ∼15% around a mean 0.7 × 10 28 s −1 value. The lifetime of H 2 O molecules against photodissociation, ∼2.5 months (Cassidy & Johnson 2010;Smith et al 2010) allows variability of the torus on comparable timescales.…”
Section: Discussion and Implications For The Source Of Water In Saturmentioning
confidence: 88%
See 1 more Smart Citation
“…Plume variability at the ∼1 order of magnitude level has been documented based on INMS and magnetic field data Saur et al 2008). In contrast, UVIS occultations (Hansen et al 2011) indicate a remarkable stability of the source rate, with variations as low as ∼15% around a mean 0.7 × 10 28 s −1 value. The lifetime of H 2 O molecules against photodissociation, ∼2.5 months (Cassidy & Johnson 2010;Smith et al 2010) allows variability of the torus on comparable timescales.…”
Section: Discussion and Implications For The Source Of Water In Saturmentioning
confidence: 88%
“…Water emitted from Enceladus' plumes in jets with 1 km s −1 velocity (Hansen et al 2008(Hansen et al , 2011 initially forms a narrow torus. However, the observed OH distribution (Melin et al 2009) requires acceleration and spreading, for which processes identified early on (Jurac & Richardson 2005;Johnson et al 2006) include the release of kinetic energy under photodissociation and collisions with rapid torus ions.…”
Section: Excitation and Torus Modelsmentioning
confidence: 99%
“…Also, Dong et al (2011) used an analytic model constrained by the same INMS observations of the E3, E5 & E7 encounters to determine source rates ranging from ~1.5 to ~3.5 x 10 28 H 2 O/sec (factor of 2). However, Hansen et al (2011) reported less than 20% plume activity variability based on Cassini Ultraviolet Imaging More recent observations appear to support plume variability. Hedman et al (2013) studied the relative brightness of dust particle observations in 252 Cassini Visual and Infrared Mapping Spectrometer (VIMS) images.…”
Section: Introductionmentioning
confidence: 82%
“…Beyond these populations, we find the classical boundary regions on the dayside (the region close to the magnetopause) and the different regions of the magnetotail on the nightside, with the With the dramatic increase in observations as a result of the Cassini mission, several studies were undertaken to better understand this primary source of magnetospheric particles. In particular, Smith et al (2010), Tensihev et al (2010) Dong et al (2011 and Hansen et al (2011) studied the Enceladus plumes using models and/or data analysis with relatively similar results. However, Smith et al (2010) showed noticeable levels of plume source variability, which now appears to be consistent with the recent Cassini dust observations reported by Hedman et al (2013).…”
Section: Introductionmentioning
confidence: 88%
“…13 If that rate were maintained over the age of the solar system, Enceladus would have ejected more than half its current inventory of ice. That is an implausibly large fraction and, like the high observed heat flow, argues that current activity rates are unusually high.…”
Section: Enceladus In Briefmentioning
confidence: 99%